2015
DOI: 10.1016/j.biortech.2015.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Combustion behavior and kinetics of low-lipid microalgae via thermogravimetric analysis

Abstract: h i g h l i g h t sCombustion of low-lipid microalgae C. pyrenoidosa and S. platensis were studied. Chemical functional groups present in two microalgae were investigated via FTIR. Apparent activation energies for combustion of the two microalgae were calculated. C. pyrenoidosa has a higher reactivity compared to S. platensis during combustion. a r t i c l e i n f o t r a c tThermogravimetric analysis and differential thermal analysis were employed to investigate combustion characteristics of two low-lipid mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 36 publications
(47 reference statements)
3
23
0
1
Order By: Relevance
“…It suggests that CP is preferable to SP during the thermal degradation process as more volatile matters could be converted into target products. And it is consistent with the results of kinetic analysis of thermal-chemical conversion of CP and SP [13,16]. According to Kumar et al [17], the solid residue is mainly composed of ash and bio-char.…”
Section: Yields Of Product Fractionssupporting
confidence: 87%
“…It suggests that CP is preferable to SP during the thermal degradation process as more volatile matters could be converted into target products. And it is consistent with the results of kinetic analysis of thermal-chemical conversion of CP and SP [13,16]. According to Kumar et al [17], the solid residue is mainly composed of ash and bio-char.…”
Section: Yields Of Product Fractionssupporting
confidence: 87%
“…Table 2 illustrated that the average value of apparent activation energy (16.34 kJ/mol) for propane was lower than that of ethylene (17.59 kJ/mol), then accompanied with methane (23.27 kJ/mol) and hydrogen (69.55 kJ/mol). The reaction rate of a reaction with lower apparent activation energy is faster due to the lesser energy required to break down the chemical bonds between atoms [39]. According to Anis and Zainal [28], the formation of hydrocarbons is more favorable than that of hydrogen during conversion of toluene, which is consistent with the results in the present study.…”
Section: Variation Of Apparent Activation Energiessupporting
confidence: 82%
“…Furthermore, several studies have shown the benefits and sustainability of the integration of microalgae pyrolysis processes within the biorefinery framework due to their capacity of integration with transesterification and fermentation processes [23][24][25]. Together with pyrolysis, microalgae combustion seems another viable technology for microalgae valorization [11,26].…”
Section: Background In Thermochemical Conversion Of Microalgae By Thementioning
confidence: 99%